Nanomaterials based biosensing: methods and principle of detection - Kumar, Nirmal; Goel, Gaurav; Goel, Saurav (Springer, 2022)
The food and medical sectors have to abide by the strict regulations of quality control and this requires strict monitoring of various types of chemicals and pathogens. These requirements have brought laurels to the field of biosensing to develop the most capable sensors to detect a target property instantly as well as precisely. Biosensors integrated with the nanotechnological approach makes them simple and tiny in size, which also provides a point-of-care platform. The last two decades have been devoted to developing different biosensors using nanoscale materials due to their sensitive and unique properties. Search is on, for the combination of materials for biosensors, which can make them multipurpose, inexpensive and eco-friendly. The molecules or analytes can be detected through different working principles of biosensors. Biosensing is a wide area and a number of biosensors exist with each having their own working principles and/or combination of two-three principles making them a hybrid sensor. This book chapter is aimed to revisit different working principles of biosensors in light of the growing use of various nanomaterials (nanoparticles, nanowire, and nanosheet) and various other materials that are in use in the development of biosensor.
Keywords: nanosheet; nanowires; nanoparticles; nanomaterials; Biosensors